2020
DOI: 10.1002/asia.201901799
|View full text |Cite
|
Sign up to set email alerts
|

Ag‐Catalyzed Trifluoromethylative Ring Expansion of Isatins and Isatin Ketimines with Trifluorodiazoethane

Abstract: A general method for the construction of trifluoromethylated 2‐quinolinones has been established herein by using a trifluoromethylative ring expansion of isatin with trifluorodiazoethane. The strategy provides a platform for the rapid synthesis of a wide range of substituted 3‐hydroxy‐4‐trifluoromethyl‐2‐quinolinones. This operationally simple and robust Ag‐catalyzed protocol successfully transforms isatin ketimines to 3‐amino‐4‐trifluoromethylquinolinones in excellent yields. The utility of this novel method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…In 2020, Mohanan reported on a reaction between in situ generated CF 3 CHN 2 (1) and isatines in the presence of AgOAc. 87 The reaction was performed at a room temperature and gave quinolinones of type 254−256 in 68−92% yield (Scheme 50). Detailed mechanistic studies were not undertaken, but the authors suggested that 2,2,2-trifluorodiazoethane reacted first with AgOAc to form intermediate 64 (Scheme 30), followed by a nucleophilic attack at the carbonyl group of isatine and the subsequent migration of the phenyl-substituent.…”
Section: Reaction With H + (Protonation)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Mohanan reported on a reaction between in situ generated CF 3 CHN 2 (1) and isatines in the presence of AgOAc. 87 The reaction was performed at a room temperature and gave quinolinones of type 254−256 in 68−92% yield (Scheme 50). Detailed mechanistic studies were not undertaken, but the authors suggested that 2,2,2-trifluorodiazoethane reacted first with AgOAc to form intermediate 64 (Scheme 30), followed by a nucleophilic attack at the carbonyl group of isatine and the subsequent migration of the phenyl-substituent.…”
Section: Reaction With H + (Protonation)mentioning
confidence: 99%
“…In 2020, Mohanan described an AgOAc-catalyzed reaction between in situ generated CF 3 CHN 2 (1) with isatine ketimines. 87 Quinolinones of type 264−266 were obtained in 68−92% yield (Scheme 53). Mechanistically, the authors proposed the formation of silver intermediate 64 (Scheme 30); however, an alternative activation of the imine moiety with Ag + could be also viable.…”
Section: Reaction With H + (Protonation)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, we developed a silver‐catalyzed ring expansive trifluoromethylation reaction of isatin 86 employing CF 3 CHN 2 to synthesize a wide range of trifluoromethylated 2‐quinolinones 87 (Scheme 42) [60]. Several isatins 86 reacted smoothly under the reaction conditions to afford this important class of compounds.…”
Section: Application Of Trifluorodiazoethane In Cf3‐heterocyclesmentioning
confidence: 99%
“…(Scheme 22, Scheme 23). [33] A range of the above products were synthesized under the optimized conditions of 5 mol % AgOAc in 1,4‐dioxane at 25 °C for 2 h in good yields. The reaction was compatible with various substitutions on the aryl ring of isatins as well as isatin ketimines and also with their N‐substituted derivatives.…”
Section: Six Membered Heterocycles With One Heteroatommentioning
confidence: 99%